STUDI ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN BERKUNJUNG WISATAWAN DOMESTIK DITINJAU DARI PERSPEKTIF DAYA TARIK DESTINASI WISATA HUTAN LINDUNG KOTA LANGSA - Agustinawati Agustinawati; Samsidar Samsidar; Halida Bahri; Mutiara Sri Devi; Zahratul Muntari (Negotium: Jurnal Ilmu Administrasi Bisnis, 2022)
This study examined the effect of tourism attractiveness on the decision to visit city forest park of Kota Langsa Tourism Destination. This study uses primary data obtained by distributing questionnaires to 100 respondents selected using the Accidental sampling method. The data analysis method used was a multiple linear regression method with the help of SPSS. The results partially showed that tourist attraction positively and significantly influenced the decision to visit the city forest park of Kota Langsa Tourism Destination Simultaneously, tourist attraction significantly influenced the decision to visit the city forest park of Kota Langsa Tourism Destination.